Phosphoproteome Profiling Reveals Circadian Clock Regulation of Posttranslational Modifications in the Murine Hippocampus - Chiang, Cheng-Kang; Xu, Bo; Mehta, Neel; Mayne, Janice; Sun, Warren Y. L.; Cheng, Kai; Ning, Zhibin; Dong, Jing; Zou, Hanfa; Cheng, Hai-Ying Mary; Figeys, Daniel (Frontiers in Neurology, 2017)
The circadian clock is an endogenous oscillator that drives daily rhythms in physiology, behavior and gene expression. The underlying mechanisms of circadian timekeeping are cell-autonomous and involve oscillatory expression of core clock genes that is driven by interconnecting transcription-translation feedback loops (TTFLs). Circadian clock TTFLs are further regulated by post-translational modifications, in particular phosphorylation. The hippocampus plays an important role in spatial memory and the conversion of short-term to long-term memory. Several studies have reported the presence of a peripheral oscillator in the hippocampus, and have highlighted the importance of circadian regulation in memory formation. Given the general importance of phosphorylation in circadian clock regulation, we performed global quantitative proteome and phosphoproteome analyses of the murine hippocampus across the circadian cycle, applying spiked-in labeled reference and high accuracy mass spectrometry. Of the 3052 proteins and 2868 phosphopeptides on 1368 proteins that were accurately quantified, 1.7% of proteins and 5.2% of phosphopeptides exhibited time-of-day-dependent expression profiles. The majority of circadian phosphopeptides displayed abrupt fluctuations at mid-to-late day without underlying rhythms of protein abundance. Bioinformatic analysis of cyclic phosphorylation events revealed their diverse distribution in different biological pathways, most notably, cytoskeletal organization and neuronal morphogenesis. This study provides the first large-scale, quantitative mass spectrometry analysis of the circadian phosphoproteome and proteome of the murine hippocampus, and highlights the significance of rhythmic regulation at the post-translational level in this peripheral oscillator. In addition to providing molecular insights into the hippocampal circadian clock, our results will assist in the understanding of genetic factors that underlie rhythms-associated pathological states of the hippocampus.